Study on the Influence of Islamic Customer Engagement and Religiosity on Customer Loyalty - Hasan, Irma Yanti (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2023)
Indonesia is the largest Muslim country in the world and Indonesia has Islamic banks which are starting to develop at this time. Islamic Bank is a Bank that carries out its business activities based on Islamic principles and according to its type consists of Islamic Commercial Bank and Sharia People’s Financing Bank. Islamic banking is a banking system developed based on Islamic Sharia (law). The effort to establish this riba and a ban on investment for businesses that are categorized as haram, which cannot be guaranteed by the conventional banking system.Islamic banks need loyal customers in order to survive and improve their performance in banking competition. The image of Islamic banks is still lagging behind conventional banks. This situation is one of the challenges of Islamic banks to develop and become a bank used by many customers both Muslim and non-Islamic. For a Muslim using Islamic banking is a religious guidance that must be obeyed and implemented. This study examines the influence of religiosity and Islamic customer engagement on the loyalty of Islamic bank customers in Malang City. Data analysis using SEM-PLS. the results indicate all hypotheses are accepted, i.e. there is a positive and significant influence between religiosity and Islamic customer engagement on loyalty imagery to loyalty.